New taxa, new records and notes on Coleoxestia Aurivillius, 1912 (Coleoptera, Cerambycidae, Cerambycinae) - Galileo, Maria Helena M.; Santos-Silva, Antonio (Zootaxa, 2016)
The following new records are reported: Coleoxestia julietae Galileo & Martins, 2006 (new department record in Bolivia; Peru, new country record); C. spinipennis spinipennis (Audinet-Serville, 1834) (Bolivia, new country record; French Guiana, new country record); C. nitida (Bates, 1872) (Bolivia, new country record); C. anthracina Martins & Monné, 2005 (Bolivia, new country record); C. glabripennis (Bates, 1870) (Peru, new country record; French Guiana, new country record); C. pubicornis (Gounelle, 1909) (Peru, new country record); C. rubromaculata (Gounelle, 1909) (Peru, new country record; French Guiana, new country record); C. rufosemivittata Tippmann, 1960 (Peru, new country record); C. illex (Gounelle, 1909) (Bolivia, new country record). Color pattern variation is reported for the first time in C. julietae and C. glabripennis (Bates, 1870). Presence of lateral spine on prothorax of Coleoxestia is reported for the first time in C. rufosemivittata Tippmann, 1960 and C. nitida. The male of C. spinifemorata Fragoso, 1993 is described. Two new species are described: C. weemsi from Trinidad and Tobago; C. bettellaorum from Bolivia.